2022
DOI: 10.1002/ange.202213942
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Better Biocatalysts by Complementing Recoded Bacteria**

Abstract: In vivo selections are powerful tools for the directed evolution of enzymes. However, the need to link enzymatic activity to cellular survival makes selections for enzymes that do not fulfill a metabolic function challenging. Here, we present an in vivo selection strategy that leverages recoded organisms addicted to non-canonical amino acids (ncAAs) to evolve biocatalysts that can provide these building blocks from synthetic precursors. We exemplify our platform by engineering carbamoylases that display cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 45 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Sequentially randomizing positions Leu217 and Phe329 enabled us to identify SmLcar_GY (named after its Leu217Gly and Phe329Tyr substitutions), which displayed shorter lag-times under selective conditions and proved >1,000-times more proficient than the wildtype carbamoylase. 16 Lastly, we also demonstrated that serial passaging could faithfully elicit SmLcar_GY from a small, controlled population containing 20 enzyme variants. 16…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Sequentially randomizing positions Leu217 and Phe329 enabled us to identify SmLcar_GY (named after its Leu217Gly and Phe329Tyr substitutions), which displayed shorter lag-times under selective conditions and proved >1,000-times more proficient than the wildtype carbamoylase. 16 Lastly, we also demonstrated that serial passaging could faithfully elicit SmLcar_GY from a small, controlled population containing 20 enzyme variants. 16…”
Section: Resultsmentioning
confidence: 63%
“…16 Lastly, we also demonstrated that serial passaging could faithfully elicit SmLcar_GY from a small, controlled population containing 20 enzyme variants. 16…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations